KANDUNGAN ALKALOID PADA AKAR DAN DAUN KECUBUNG (Datura metelL.) SETELAH PERLAKUAN TEMBAGA - , EVA FATIHATUR ROHMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Copper is one of heavy metals thats widely used in industrial and agricultural activities. Increased copper were exposed to environment causes toxicity to organisms. Plants are organisms sensitive to the environmental changes. Datura metel L. is one of the heavy metals tolerant plant and has the potential as phytoremediation agent. Alkaloid is one of the secondary metabolites produced by D. metel as a self-defense compund against abiotic and biotic stress. The purpose of this study was to determine the alkaloid content of Datura metel in the root and the leave after treatment Cu. Datura seedlings were treated with heavy metal with concentrations of 0, 100, 1000, 2000, and 2500 ppm for the duration of 12, 36, 84, and 132 hours. Morphological leave were observed for the present of chlorosis and alkaloid was done by Bromocressol green (BCG) method using spectrophotometer. The results showed that the number of Datura leave suffered chlorosis increased with the increase concentration and length exposure. The accumulation of copper by Datura occurred on root with the highest accumulation was 0,04 mg/kg at 2500 ppm concentration. The increasing alkaloid contents was present higher in the roots and transferred to the leaves following the concentration. The treatment 2500 ppm concentration increased the alkaloid contents in general. The results indicated that Datura metel had high tolerants against high concentration of copper.